Evaluation of risk factors for obstruction of the intraventricular catheter after ventriculoperitoneal shunting in dogs with congenital internal hydrocephalus - Siwicka, Anna K.; Farke, Daniela; Büttner, Kathrin; Moritz, Andreas; Schmidt, Martin J. (Frontiers in Veterinary Science, 2026)
BackgroundVentriculoperitoneal shunting (VPS) is the standard treatment for congenital internal hydrocephalus in dogs; however, obstruction of the ventricular catheter is a frequent and serious complication. In human medicine, several predictors of catheter obstruction have been identified, while corresponding risk factors in veterinary patients remain largely unknown.ObjectivesThis study aimed to identify potential risk factors for ventricular catheter obstruction after VPS implantation in dogs with congenital internal hydrocephalus.MethodsA retrospective cohort study was conducted involving 100 client-owned dogs diagnosed with congenital internal hydrocephalus and treated with VPS implantation between 2001 and 2022. The medical records and magnetic resonance imaging (MRI) data of these dogs were reviewed for age, sex, breed, body weight, ventricular size, ventricular catheter position, and preoperative medical treatments. Cerebrospinal fluid (CSF) samples were analyzed for cell count, red blood cell count, protein concentration, and cytology before and after surgery. Single logistic regression and chi-squared tests were performed to evaluate associations with ventricular catheter obstruction.ResultsObstruction occurred in 9 of the 100 dogs examined (9%; 95% confidence interval 3–15%), with an onset ranging from 8 to 210 days after VPS surgery (median 38 days). No significant associations were found between demographic factors, ventricle-to-brain ratio, ventricular catheter position, preoperative medical treatment, or CSF parameters and the occurrence of obstruction. Cerebrospinal fluid analysis revealed marked postoperative increases in cell counts, protein concentration, and red blood cell counts, peaking within the first week after surgery and gradually returning to reference ranges at the 3-month follow-up. Histological examination of obstructed catheters in three dogs demonstrated intraluminal blockage caused by inflammatory infiltrates, fibrin, and choroid plexus cells.ConclusionObstruction of the ventricular catheter remains a clinically important complication after VPS implantation in dogs with internal hydrocephalus. No definitive risk factors could be identified in this study. The observed postoperative CSF changes appear to reflect inflammatory and surgical responses rather than being predictors of obstruction. Further investigations with larger case numbers and detailed immunological analyses are required to clarify the underlying mechanisms and to improve prevention strategies.